PERLINDUNGAN HUKUM DATA PRIBADI TERHADAP PENYALAHGUNAAN DATA PRIBADI PADA PLATFORM MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEK - Lydia Kharista Saragih; Danrivanto Budhijanto; Somawijaya Somawijaya (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
Abstract Amid the development of technology, the use of social media is increasing. Information on social media can be easily obtained including a person's personal data and privacy matters. This certainly triggers the misuse of personal data when interacting between social media users. Even though personal data are part of human rights that should be protected. This study aims to analyze the extent to which the government provides legal protection for personal data against misuse of personal data on social media platforms based on the ITE Law and how legal actions can be taken by victims for misuse of personal data on social media platforms. The author uses the normative juridical research method through the review of invitations to settle upon the matter. Based on the results of the study, the government has not provided maximum legal protection for personal data for the society against the misuse of personal data, especially those that occur on social media platforms. The establishment of a clear and comprehensive law is needed to determine definite steps in the process of using personal data in order to provide legal certainty to protect personal data of society. Legal actions that victims can take for misuse of personal data on social media platforms provided by the law are still limited to carrying out lawsuits and demanding administrative sanctions. Keyword: Legal Protection, Personal Data, Privacy, Social Media.